Italo Calvino, Julio Cortazar, and the Nouveau Roman - Pujol-Duran, J (De Gruyter, 2024)
Julio Cortazar and Italo Calvino, friends and foreign writers living in Paris in the 1960s and 1970s, performed a number of literary experiments throughout their time in the city that share a deep connection with the writers of the nouveau roman. Its most representative author, Alain Robbe-Grillet, dedicated a series of essays to defining the poetics of this new writing, such as "A quoi servent les theories" (1955) and "Nouveau roman, homme nouveau" (1961), which lie at the centre of my analysis. Calvino and Cortazar read the nouveau roman writers and reflected upon Robbe-Grillet s stylistic principles, as I will explain by performing a close reading of Cortazar s Historias de cronopios y famas (1962) and 62: Modelo para armar (1968) as well as Calvino s Le cosmicomiche (1968). I will also, however, argue that, at the same time, they both chose to disassociate themselves from Robbe-Grillet s ideas in favour of a more subjective and anthropological conception of literature. A comparative study of their reactions to the nouveau roman movement will thus provide an understanding of their wider practices, and we will see how their writing moved away from the rubrics of the nouveau roman with which they both have been frequently associated. © 2024 the author(s), published by De Gruyter. All rights reserved.